2014
DOI: 10.1021/ja411699u
|View full text |Cite
|
Sign up to set email alerts
|

Distortion/Interaction Analysis Reveals the Origins of Selectivities in Iridium-Catalyzed C–H Borylation of Substituted Arenes and 5-Membered Heterocycles

Abstract: The iridium-catalyzed borylation of mono-and disubstituted arenes and heteroarenes has been studied with density functional theory. The distortion/interaction model was employed to understand the origins of selectivities in these reactions. Computations revealed that the transition states for C−H oxidative addition are very late, resembling the aryl iridium hydride intermediate with a fully formed Ir−C bond. Consequently, the regioselectivity is mainly controlled by differences in the interaction energies betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
152
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(157 citation statements)
references
References 50 publications
0
152
0
2
Order By: Relevance
“…f). (5) B(3,6)–H bonds were more reactive than B(4,5,7,11)–H ones in the above borylation, suggesting that the activation of cage B–H bond may proceed via oxidative addition pathway136373839555657, instead of electrophilic substitution mechanism303132333435 as the electron density in o -carborane follows the trend: B(3,6)<B(4,5,7,11)<B(8,10)<B(9,12)127.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…f). (5) B(3,6)–H bonds were more reactive than B(4,5,7,11)–H ones in the above borylation, suggesting that the activation of cage B–H bond may proceed via oxidative addition pathway136373839555657, instead of electrophilic substitution mechanism303132333435 as the electron density in o -carborane follows the trend: B(3,6)<B(4,5,7,11)<B(8,10)<B(9,12)127.…”
Section: Resultsmentioning
confidence: 98%
“…On the basis of the aforementioned experimental results and literature work303645464748495051525354555657, a proposed mechanism for the borylation reaction is shown in Fig. 5.…”
Section: Resultsmentioning
confidence: 98%
“…561 In a related study in 2014, Merlic, Houk, and co-workers investigated the borylation of substituted arenes and heterocycles. 562 Their computations at the SMD (n-octane) M06/6-311G(d,p)(SDD)//B3LYP/6-31G(d)(LANL2DZ) level of theory suggested that C−H oxidative addition transition states are very late and in close resemblance to the aryl Ir hydride intermediate. Thus, regioselectivity is mainly interaction energy controlled.…”
Section: Allylic Substitutionmentioning
confidence: 99%
“…Also, the C(sp Another important development is to achieve regioselective CH σ-bond activation in these direct borylation reactions, which is also an important target in the chemistry of CH activation because regioselective CH σ-bond activation is not easy. The factors for controlling regioselectivity have been discussed in theoretical work of borylation of substituted arenes, heterocycles, 119 and chlorosilane. 117 In the direct borylation of alkylamines and alkylethers, the regioselectivity has been experimentally and theoretically well investigated.…”
Section: Catalyses For Hydrosilylation Of Alkenementioning
confidence: 99%